2020
DOI: 10.3892/ijmm.2020.4458
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑3651 promotes colorectal cancer cell proliferation through directly repressing T‑box transcription factor 1

Abstract: colorectal cancer is a commonly diagnosed gastrointestinal malignancy worldwide with a high mortality rate. Accumulating evidence has indicated that the expression of a number of microRNAs (miRNAs) is associated with the development of colorectal cancer. However, the precise molecular mechanism of these miRNAs in regulating cancer progression is yet to be determined. In the present study, miR-3651 was demonstrated to be overexpressed in colorectal cancer tissues compared with normal tissues, and to be associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Western blot in this study also showed that decreased expression of this marker leads to inactivation of PI3K / AKT and MAPK / ERK signaling pathways in colorectal cancer cells. Finally, this study suggested that this marker has oncogenic potential in colorectal cancer (33).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Western blot in this study also showed that decreased expression of this marker leads to inactivation of PI3K / AKT and MAPK / ERK signaling pathways in colorectal cancer cells. Finally, this study suggested that this marker has oncogenic potential in colorectal cancer (33).…”
Section: Discussionmentioning
confidence: 54%
“…It is located in the nucleus of a human cell on chromosome 9 (9q22.31) and is estimated to be 24 nucleotides in length. Changes in the expression of this miRNA have been studied in various cancers, including esophageal cancer (25), nasopharynx (29), liver cells (32) and colorectal (30,33). Also, according to articles that examined such biomarkers in precancerous lesions compared to cancerous and normal tissue, and observed changes in the incidence of these biomarkers (31), resulting in the possibility of changes in the expression of this miRNA in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated microRNA–T-box member regulatory modulation in several biological contexts in both homeostasis and diseases, in particular for Tbx1 , Tbx3 , and Tbx5 . Tbx1 is targeted by miR-3651 in colorectal cancer, promoting cell proliferation [ 62 ]; by miR-451a in cutaneous basal carcinoma, suppressing cell growth [ 63 ]; and by miR-96 in dental epithelial progenitor cells [ 64 ]. In addition, indirect evidence supports a role of the miR-17-92 cluster in the regulation of Tbx1 expression during midface development [ 68 ] and for miR-182 during otocyst-derived cell differentiation [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among those T-box genes expressed during cardiogenesis, microRNA-mediated post-transcriptional regulation has only been reported for Tbx1 , Tbx3 , and Tbx5 in distinct biological contexts. Tbx1 is targeted by miR-3651 in colorectal cancer, promoting cell proliferation [ 62 ]; by miR-451a in cutaneous basal carcinoma, suppressing cell growth [ 63 ]; and by miR-96 in dental epithelial progenitor cells [ 64 ]. Furthermore, only indirect evidence supports a role of the miR-17-92 cluster in regulation of Tbx1 expression during myocardial differentiation from cardiac progenitors [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRs) are small noncoding RNAs that can target the 3ʹ untranslated region (3ʹUTR) of message RNAs (mRNAs) to degrade mRNAs and/or inhibit mRNA translation. Until now, several studies have reported the roles of miRs in cell proliferation, migration, invasion, and angiogenesis of CC [19][20][21]. Our previous study demonstrated that miR-6727-5p was highly expressed in CC tissues and promoted the proliferation of CC cells [22].…”
Section: Introductionmentioning
confidence: 99%